The storage compounds associated with Tetrasphaera PAO metabolism and the relationship between diversity and P removal. (1st October 2021) - Close, Kylie; Marques, Ricardo; Carvalho, Virginia C.F.; Freitas, Elisabete B.; Reis, Maria A.M.; Carvalho, Gilda; Oehmen, Adrian
Abstract: In enhanced biological phosphorus removal (EBPR), Tetrasphaera can potentially be an abundant and important polyphosphate accumulating organism (PAO), however ongoing questions remain concerning its storage compounds, phosphorus (P) removal capabilities and metabolic behaviour. This study investigated each of these points in an enriched Tetrasphaera culture (95% biovolume). The enriched Tetrasphaera culture fermented amino acids, while also converting and storing diverse amino acids as aspartic and glutamic acid within cells. Subsequent intracellular consumption of these two amino acids during the aerobic phase supports their importance in the metabolism of Tetrasphaera. Polyhydroxyalkanoate (PHA) cycling was also observed in this study, in contrast to some previous studies on Tetrasphaera. While exhibiting anaerobic phosphorus release and aerobic uptake, the highly enriched Tetrasphaera culture was unable to completely remove phosphorus in sequencing batch reactors (SBR) cycles, with an average removal efficiency of 72.3 ± 7.8%. This is unlike a previous study containing both Tetrasphaera (70%) and Accumulibacter (22%), which regularly performed complete phosphorus removal under otherwise similar operational conditions, at efficiencies of > 99%. Notably, the phylodiversity of organisms belonging to Tetrasphaera was substantially different in the present work, consisting mainly of organisms within Clade 2, likely impacting PHA cycling. These results suggest that the contribution of Tetrasphaera towards P removal is highly dependent on the composition of its Clades within this microbial group and an observed higher abundance of Tetrasphaera in WWTPs does not necessarily imply overall higher P removal. This study improves our understanding of the role of Tetrasphaera within EBPR systems and key factors impacting its metabolism.